Differential Activation and Regulation of CXCR1 and CXCR2 by CXCL8 monomer and dimer - Nasser, Mohd W. (2009)
CXCL8 (also known as interleukin-8) activates CXCR1 and CXCR2 to mediate neutrophil recruitment and trigger cytotoxic effect at sites of infection. Under physiological conditions, CXCL8 could exist as monomers, dimers, or a mixture of monomers and dimers. Therefore, both forms of CXCL8 could interact with CXCR1 and CXCR2 with different affinities and potencies to mediate different cellular responses. In the present study, we have used a “trapped” non-associating monomer (L25NMe), and a non-dissociating dimer (R26C), to investigate their activities for human neutrophils which express both receptors, and for RBL-2H3 cells stably expressing either CXCR1(RBL-CXCR1) or CXCR2 (RBL-CXCR2). The monomer was more active than the dimer for activities such as intracellular Ca(2+) mobilization, phosphoinositide hydrolysis, chemotaxis and exocytosis. Receptor regulation, however, is distinct for each receptor. The rate of monomer-mediated regulation of CXCR1 is greater for activities such as phosphorylation, desensitization, βarrestin translocation and internalization. In contrast, for CXCR2, both monomeric and dimeric CXCL8 mediate these activities to similar extent. Interestingly, receptor-mediated signal-regulated kinases (ERK) phosphorylation in response to all three CXCL8 variants was more sustained for CXCR2 relative to CXCR1. Taken together, the results indicate that the CXCL8 monomer and dimer differentially activate and regulate CXCR1 and CXCR2 receptors. These distinct properties of the ligand and the receptors play a critical role in orchestrating neutrophil recruitment and eliciting cytotoxic activity during an inflammatory response